Decoronation followed by dental implants placement: fundamentals, applications and explanations - Alberto Consolaro; Paulo Domingos Ribeiro Júnior; Maurício A. Cardoso; Dario A. Oliveira Miranda; Monica Salfatis
ABSTRACT Dental arches areas with teeth presenting dentoalveolar ankylosis and replacement root resorption can be considered as presenting normal bone, in full physiological remodeling process; and osseointegrated implants can be successfully placed. Bone remodeling will promote osseointegration, regardless of presenting ankylosis and/or replacement root resorption. After 1 to 10 years, all dental tissues will have been replaced by bone. The site, angulation and ideal positioning in the space to place the implant should be dictated exclusively by the clinical convenience, associated with previous planning. One of the advantages of decoronation followed by dental implants placement in ankylosed teeth with replacement resorption is the maintenance of bone volume in the region, both vertical and horizontal. If possible, the buccal part of the root, even if thin, should be preserved in the preparation of the cavity for the implant, as this will maintain gingival tissues looking fully normal for long periods. In the selection of cases for decoronation, the absence of microbial contamination in the region - represented by chronic periapical lesions, presence of fistula, old unconsolidated root fractures and active advanced periodontal disease - is important. Such situations are contraindications to decoronation. However, the occurrence of dentoalveolar ankylosis and replacement resorption without contamination should neither change the planning for implant installation, nor the criteria for choosing the type and brand of dental implant to be used. Failure to decoronate and use dental implants has never been reported.